Pengaruh kecukupan modal dan efisiensi operasional terhadap kinerja keuangan perbankan umum konvensional di Bursa Efek Indonesia Periode 2016-2020 - Ulfan Nurkhalifa; Asep Machpudin; Rike Setiawati (Jurnal Dinamika Manajemen, 2021)
Banking has an important role in the economy, this can be seen from when a sector experiences a decline, then an effort is made to restore economic growth by organizing the banking sector. This study aims to find out empirically the effect of Capital Adequacy (CAR) and Operational Efficiency (BOPO) on Banking Financial Performance (ROA) of conventional commercial banks listed on the Indonesia Stock Exchange, 2016-2020 research period. This research is a quantitative associative causality research. The method used is purposive sampling method. Based on the established criteria, there are 21 banks out of 41 population of conventional commercial banks that meet the criteria. This research uses Multiple Linear Regression analysis technique with SPSS method. The results of this study indicate that (1) Capital adequacy (CAR) has no significant effect on banking financial performance (ROA) shows a significant value of 0.474 (2) operational efficiency (BOPO) has a significant effect on banking financial performance (ROA) shows a significant value of 0.000 .